Salt-tolerant and temperature-tolerant hybrid hydrogel plugging agent, preparation method and application thereof

CN122381785BActive Publication Date: 2026-10-13CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610866951.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-10-13
Estimated Expiration
2046-06-16

AI Technical Summary

Technical Problem

[0004](1)凝胶体系结构强度与长期稳定性差

Benefits of technology

[0029](1)实现了高温高盐环境下成胶时间的精确可控。现有技术中,高温会急剧加速引发剂分解,导致体系在井筒中提前“爆聚”成胶,施工风险极高。本发明创新性地采用疏水缔合聚合物包裹水溶性高温引发剂构成缓释胶囊,利用高矿化度地层水缓慢溶解胶囊壁材,逐步释放引发剂,从而将高温下的成胶时间有效调控在安全窗口内,保障了施工安全。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122381785B_ABST
    Figure CN122381785B_ABST
Patent Text Reader

Abstract

The application provides a kind of salt-tolerant and temperature-tolerant hybrid hydrogel plugging agent and its preparation method and application, and belongs to the field of oilfield water plugging.The plugging agent comprises the following components in mass fraction: 1.5-3 parts of acrylamide, 1.5-2.5 parts of chain enhancer, 1.5-2.5 parts of multi-active site reaction monomer, 0.08-0.15 parts of crosslinking agent N,N'-methylene bisacrylamide, 2-3 parts of inorganic structure supporting material, 0.8-1.8 parts of slow-release capsule initiation system, and 90-95 parts of formation water.The plugging agent can control the gelation time in a high-temperature and high-salt environment, so as to effectively regulate the gelation time within a safe window and ensure the safety of construction.The plugging agent constructs a "stiffness-elasticity-toughness" matched reinforced gel network, has high plugging strength, excellent temperature resistance and salt resistance, and good fluidity and injectivity, and is convenient for on-site mixing and pumping.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water shut-off in oilfields, and particularly to a salt- and temperature-resistant hybrid hydrogel plugging agent, its preparation method, and its application. Background Technology

[0002] Fractured-vuggy carbonate reservoirs have extremely complex geological conditions, characterized by "ultra-deep, ultra-high temperature, and ultra-high salinity": burial depths reach 5000-8000 meters, formation temperatures reach 120-150℃, and formation water salinity exceeds 21×10⁻⁶. 4 mg / L, and rich in Ca 2+ Mg 2+ Ions. In this type of reservoir, large fractures and caves are widely developed, the reservoir water body has abundant energy and obvious dominant channels, resulting in extremely low effectiveness of conventional water shut-off measures, only 28%.

[0003] Although polymer hydrogel plugging systems have been widely studied due to their cost advantages, existing technologies have the following technical shortcomings that urgently need to be addressed when facing the aforementioned extreme working conditions:

[0004] (1) Poor structural strength and long-term stability of gel structures. In high-temperature and high-salt environments, the amide groups in the molecular chains of traditional polymer gels (such as polyacrylamide) are prone to hydrolysis. The resulting carboxylic acid groups combine with calcium and magnesium ions in the formation water to form precipitates, leading to the destruction of the gel network structure and resulting in dehydration shrinkage or even collapse. Conventional Cr... 3+ Crosslinked HPAM gels rely on ionic bonding for crosslinking, resulting in a significant decrease in thermal stability at high temperatures. Even when organic crosslinking agents are used, the reaction sites still depend on amide groups, which inevitably undergo hydrolysis at high temperatures. Ultimately, this leads to the gel's sealing strength failing to meet the requirements for supporting subsequent plugging agents, and its long-term effectiveness cannot be guaranteed.

[0005] (2) Uncontrolled gelation time leads to high construction risks. The successful pumping of the plugging agent to the target formation is a prerequisite for successful operation. However, at temperatures of 140℃ and above, the decomposition rate of initiators for conventional free radical polymerization (such as persulfate) accelerates dramatically, resulting in excessively rapid polymerization and a significantly shortened gelation time to less than one hour. This causes the system to undergo "explosive polymerization" and gel prematurely during wellbore transport, easily leading to serious engineering accidents, wellbore blockage, and jeopardizing the safe construction window.

[0006] (3) The system has weak resistance to dilution and is difficult to remain effectively in crevices. To improve injectability, traditional gel working solutions usually have a low initial viscosity. During injection, its leading edge is easily diluted by high-intensity edge and bottom water, resulting in a decrease in the concentration of effective ingredients, poor gel quality, or even failure to gel. Research has found that attempts to increase viscosity by adding inorganic materials such as bentonite to resist dilution are ineffective in ultra-high mineralization (>21×10⁻⁶).4 It completely fails under conditions of (mg / L). This is because a sharp increase in electrolyte concentration compresses the electric double layer of clay particles, inhibiting their hydration and dispersion, leading to precipitation and stratification of the system, which in turn worsens the overall performance.

[0007] For example, Chinese patent document CN 111117582 A discloses a controllable crosslinking gel plugging agent and its preparation method. The controllable crosslinking gel plugging agent comprises the following components: vinyl monomer, N,N-methylenebisacrylamide, and a crosslinking agent. The preparation steps are: 1) under the action of an initiator, the vinyl monomer and N,N-methylenebisacrylamide are reacted to obtain a polymer main agent; 2) the polymer main agent and the crosslinking agent are mixed and reacted at a certain temperature to obtain the gel plugging agent. This invention's controllable crosslinking gel plugging agent has a controllable crosslinking time and also has advantages such as good fluidity and ease of pumping. Under formation temperature and pressure, it can be squeezed into the leaking layer to form a monolithic, immovable gel, thereby improving pressure resistance and sealing effect, and reducing the likelihood of repeated leakage. However, this invention's plugging agent still has the problem of a relatively fast melting time under high temperature conditions, and its high-temperature resistance is only 100℃, indicating insufficient high-temperature performance. It also does not address salt resistance-related properties.

[0008] Therefore, developing a new type of plugging system that can adapt to ultra-high temperature and ultra-high mineralization environments, with controllable gelation time, high structural strength, and strong erosion resistance is crucial and urgent for improving the success rate of water plugging operations and development benefits in fractured reservoirs in oil fields. Summary of the Invention

[0009] To address the shortcomings of existing technologies, this invention provides a salt- and temperature-resistant hybrid hydrogel plugging agent, its preparation method, and its applications. The plugging agent of this invention exhibits controllable gelation time under high-temperature and high-salt environments, effectively regulating the gelation time within a safe window and ensuring construction safety. The plugging agent of this invention constructs a reinforced gel network with matched stiffness, elasticity, and toughness, resulting in high plugging strength and excellent temperature and salt resistance; it also possesses good flowability and injectability, facilitating on-site mixing and pumping.

[0010] The technical solution of the present invention is as follows:

[0011] In a first aspect, the present invention provides a salt- and temperature-resistant hybrid hydrogel plugging agent, comprising the following components in parts by weight:

[0012] Acrylamide (AM) 1.5-3 parts, chain reinforcer 1.5-2.5 parts, multi-active-site reactive monomer 1.5-2.5 parts, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.08-0.15 parts, inorganic structural support material 2-3 parts, sustained-release capsule initiation system 0.8-1.8 parts, formation water 90-95 parts.

[0013] According to a preferred embodiment of the present invention, the chain enhancer is pregelatinized starch.

[0014] According to a preferred embodiment of the present invention, the multi-active-site reactive monomer is selected from one or more combinations of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), N-hydroxymethylacrylamide (NHMA), or N-hydroxymethylmethylacrylamide (NHMMA).

[0015] According to a preferred embodiment of the present invention, the inorganic structural support material is a silicon-containing inorganic structural support material; preferably, the inorganic structural support material is selected from one or more combinations of nano-silica, silica fume, silica sol, silica powder or layered silicate minerals (montmorillonite); the nano-silica is selected from one or two of precipitated silica or fumed silica.

[0016] According to a preferred embodiment of the present invention, the core material of the sustained-release capsule initiation system is a water-soluble high-temperature initiator tert-butyl hydroperoxide (TBHP), and the wall material is a hydrophobic associating polymer; the hydrophobic associating polymer is a copolymer of acrylamide-acrylic acid-octadecyl dimethyl allyl ammonium chloride-vinylpyrrolidone.

[0017] According to a preferred embodiment of the present invention, the preparation method of the sustained-release capsule initiation system includes the following steps: dissolving acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, vinylpyrrolidone (NVP), sodium formate, urea and tert-butyl hydroperoxide (TBHP) in deionized water, adjusting the pH to 7.0, adding ammonium persulfate, reacting, shearing and pulverizing, drying and sieving to obtain the sustained-release capsule initiation system.

[0018] Preferably, the mass ratio of acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, and vinylpyrrolidone (NVP) is 45:5-10:3-8:10-15, more preferably 45:8:5:12; the mass ratio of acrylamide (AM), sodium formate, and urea is 45:1-5:1-5, more preferably 45:2:3; and the mass ratio of acrylamide to deionized water is 45:150-250, more preferably 45:200.

[0019] Preferably, the mass of ammonium persulfate is 0.5-1% of the total mass of acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, and vinylpyrrolidone (NVP), more preferably 0.71%.

[0020] Preferably, the mass of tert-butyl hydroperoxide (TBHP) is 20-25% of the total mass of acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, and vinylpyrrolidone (NVP), more preferably 21.4%.

[0021] Preferably, the pH is adjusted using a 5-15 wt% sodium hydroxide aqueous solution.

[0022] Preferably, the reaction temperature is 35-45℃, the reaction time is 4-6 hours, and the reaction is carried out under the protection of an oxygen-free protective gas and stirring. The protective gas is nitrogen or argon.

[0023] Preferably, the sieve is a 100-mesh sieve.

[0024] According to a preferred embodiment of the present invention, the salinity of the formation water is 0.5 × 10⁻⁶. 5 -2.5×10 5 mg / L.

[0025] Secondly, the present invention provides a method for preparing the above-mentioned salt- and temperature-resistant hybrid hydrogel plugging agent, comprising the steps of:

[0026] Chain enhancer, acrylamide (AM), multi-active site reactive monomer, crosslinking agent N,N'-methylenebisacrylamide, and sustained-release capsule initiation system were added sequentially to the formation water, and the mixture was stirred continuously until it was fully mixed and dispersed. Then, inorganic structural support material was added and fully dispersed to obtain salt- and temperature-resistant hybrid hydrogel plugging agent.

[0027] Thirdly, the present invention provides the application of the above-mentioned salt-resistant and temperature-resistant hybrid hydrogel plugging agent in reservoir water plugging.

[0028] Technical features and beneficial effects of the present invention:

[0029] (1) Precise control of gelation time under high temperature and high salinity conditions has been achieved. In the prior art, high temperature will accelerate the decomposition of the initiator, causing the system to "explode" and gel prematurely in the wellbore, resulting in extremely high construction risks. This invention innovatively uses hydrophobic associative polymers to encapsulate water-soluble high-temperature initiators to form sustained-release capsules. The capsule wall material is slowly dissolved by high-mineralization formation water, gradually releasing the initiator, thereby effectively controlling the gelation time under high temperature within a safe window and ensuring construction safety.

[0030] (2) A reinforced gel network with matched stiffness, elasticity, and toughness was constructed, resulting in high sealing strength. Traditional gel systems suffer severe strength degradation under high temperature and high salt conditions. This invention achieves hybridization by grafting acrylamide with chain reinforcing agents (modified starch) and multi-active-site reactive monomers, and by introducing inorganic structural support materials, forming a stable multi-level, multi-crosslinked network. The system exhibits a peak compressive strength higher than 0.076 MPa and an elastic deformation capacity greater than 70%, demonstrating excellent mechanical properties and erosion resistance.

[0031] (3) It has excellent temperature and salt resistance. In view of the problems of easy hydrolysis of amide groups and easy precipitation of divalent ions, the present invention introduces a chain reinforcing agent with a cyclic structure and stable covalent crosslinking, and combines the supporting role of an inorganic rigid skeleton, so that the plugging agent has good mechanical properties after gelation under high temperature and high salt conditions, that is, it has excellent temperature and salt resistance.

[0032] (4) Raw material costs are controllable, and on-site operation is highly feasible. The selected chain enhancers (modified starch) and other main agents are inexpensive. The working solution density is 1.1-1.2 g / cm³. 3 With a viscosity between 40 and 800 mPa·s, it has good flowability and injectability, making it easy to mix and pump on site.

[0033] (5) The specific types of raw materials of the present invention work together in a specific ratio to achieve the excellent effect of the present invention; if the types and ratios of raw materials are not suitable, or if a certain raw material is omitted, the performance of the resulting plugging agent will be reduced. Attached Figure Description

[0034] Figure 1 A photograph of the hydrogel plugging agent prepared in Example 1 after curing.

[0035] Figure 2 This is a scanning electron microscope image of the sealant prepared in Example 1 after curing.

[0036] Figure 3 The image shows the EDS spectrum of the hydrogel plugging agent prepared in Example 1 after curing.

[0037] Figure 4 The image shows the sealing test results of the hydrogel plugging agent prepared in Example 1.

[0038] Figure 5 The image shows the strength test result of the hydrogel plugging agent prepared in Example 1 after curing.

[0039] Figure 6 The rheological test diagram is shown for the hydrogel plugging agent prepared in Example 1. Detailed Implementation

[0040] The present invention will be further described below with reference to the embodiments. However, the embodiments of the present invention are merely illustrative examples and should not be construed as limiting the present invention under any circumstances.

[0041] Example 1

[0042] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0043] Acrylamide (AM) 2g, chain enhancer pregelatinized starch 2g, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 2g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.1g, nano-fumed silica (particle size 7-40 nm) 2.5g, sustained-release capsule initiation system 1.5g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0044] The preparation method of the sustained-release capsule initiation system includes the following steps:

[0045] The following components were added sequentially to a reactor equipped with a stirrer, thermometer, and nitrogen inlet: 45g acrylamide (AM), 8g acrylic acid (AA), 5g hydrophobic monomer (octadecyl dimethyl allyl ammonium chloride), 12g vinylpyrrolidone (NVP), 2g sodium formate, 3g urea, 15g tert-butyl hydroperoxide (TBHP), and 200mL deionized water, and the mixture was thoroughly dispersed. The pH was adjusted to 7.0 with a 10wt% sodium hydroxide aqueous solution, and nitrogen was introduced to purge oxygen for 30 minutes. Under nitrogen protection, 0.5g of initiator ammonium persulfate was added, and the mixture was stirred and reacted in a 40°C water bath for 5 hours to obtain a colloidal product. The obtained product was sheared and pulverized, dried in a 50°C vacuum drying oven for 6 hours, and passed through a 100-mesh sieve to obtain the sustained-release capsule initiation system powder.

[0046] The preparation method of the above-mentioned salt- and temperature-resistant hybrid hydrogel plugging agent includes the following steps:

[0047] Chain-reinforcing pregelatinized starch, acrylamide (AM), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), crosslinking agent N,N'-methylenebisacrylamide (MBA), and sustained-release capsule initiation system were added sequentially to the formation water. After stirring until fully dispersed, nano-fumed silica was added, and stirring was continued for 15 minutes to obtain a homogeneous working solution, namely a salt- and temperature-resistant hybrid hydrogel plugging agent.

[0048] The above-mentioned salt- and temperature-resistant hybrid hydrogel plugging agent working solution was injected into a capped glass bottle and sealed. It was then placed in a 140°C constant temperature oven and allowed to react for 4 hours until complete gelation. After cooling to room temperature, it was removed and photographed. Figure 1 As shown, the gel is formed as a whole and there is no obvious water separation.

[0049] The above-mentioned salt- and heat-resistant hybrid hydrogel plugging agent working solution was placed in a 140℃ constant temperature oven and allowed to react for 4 hours until complete gelation. The gelled sample was cut into blocks of approximately 5 mm × 5 mm, frozen at -50℃, and then freeze-dried for 48 hours. After gold sputtering, SEM testing was performed. The SEM image is shown below. Figure 2 As shown in the figure, the inorganic structural support material is uniformly attached to the surface of the polymer network structure, reinforcing the structural support framework.

[0050] The above-mentioned salt- and heat-resistant hybrid hydrogel plugging agent working solution was placed in a 140℃ constant temperature oven and allowed to react for 4 h until complete gelation. The gelled sample was then frozen at -50℃ and freeze-dried for 48 h, followed by EDS testing. The EDS spectrum is shown below. Figure 3 As shown. Figure 3 As shown in (a), within the scanning region, Si elements exhibit a highly uniform and continuous distribution, with dense signal points covering a wide area. The highly dispersed Si elements form ubiquitous rigid support points, constituting a continuous "inorganic framework." This framework effectively distributes and dissipates external stress. Figure 3 As shown in (b) and (c), Ca from formation water 2+ and Mg 2+ The ions also showed a uniform distribution without obvious local aggregation or precipitation, indicating that the gel formed a dense and stable three-dimensional network, successfully "fixing" high-valence metal ions inside the gel and preventing them from destroying the structure.

[0051] Example 2

[0052] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0053] Acrylamide (AM) 3g, chain enhancer pregelatinized starch 1.5g, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 1.5g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.12g, nano-fumed silica 2g, sustained-release capsule initiation system 1.2g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0054] The preparation method of the sustained-release capsule initiation system is the same as in Example 1.

[0055] The preparation method of the above-mentioned salt-resistant and temperature-resistant hybrid hydrogel plugging agent is the same as that in Example 1.

[0056] Example 3

[0057] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0058] Acrylamide (AM) 1.5g, chain enhancer pregelatinized starch 2.5g, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 2g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.08g, nano-fumed silica 3g, sustained-release capsule initiation system 1.8g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0059] The preparation method of the sustained-release capsule initiation system is the same as in Example 1.

[0060] The preparation method of the above-mentioned salt-resistant and temperature-resistant hybrid hydrogel plugging agent is the same as that in Example 1.

[0061] Example 4

[0062] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0063] Acrylamide (AM) 2g, chain enhancer pregelatinized starch 2g, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 2.5g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.15g, nano-fumed silica 2g, sustained-release capsule initiation system 1g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0064] The preparation method of the sustained-release capsule initiation system is the same as in Example 1.

[0065] The preparation method of the above-mentioned salt-resistant and temperature-resistant hybrid hydrogel plugging agent is the same as that in Example 1.

[0066] Example 5

[0067] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0068] Acrylamide (AM) 2.5g, chain enhancer pregelatinized starch 2g, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 1.5g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.1g, nano-fumed silica 2.5g, sustained-release capsule initiation system 1.5g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0069] The preparation method of the sustained-release capsule initiation system is the same as in Example 1.

[0070] The preparation method of the above-mentioned salt-resistant and temperature-resistant hybrid hydrogel plugging agent is the same as that in Example 1.

[0071] Example 6

[0072] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0073] Acrylamide (AM) 2g, chain enhancer pregelatinized starch 2g, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 2g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.1g, nano-fumed silica 2.5g, sustained-release capsule initiation system 0.8g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0074] The preparation method of the sustained-release capsule initiation system is the same as in Example 1.

[0075] The preparation method of the above-mentioned salt-resistant and temperature-resistant hybrid hydrogel plugging agent is the same as that in Example 1.

[0076] Example 7

[0077] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0078] Acrylamide (AM) 2g, chain enhancer pregelatinized starch 2g, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 2g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.1g, silica powder (particle size D50≤5 μm) 2.5g, sustained-release capsule initiation system 1.5g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0079] The preparation method of the sustained-release capsule initiation system is the same as in Example 1.

[0080] The preparation method of the above-mentioned plugging agent includes the following steps:

[0081] Chain enhancer pregelatinized starch, acrylamide (AM), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), crosslinking agent N,N'-methylenebisacrylamide (MBA), and sustained-release capsule initiation system were added sequentially to the formation water. After stirring until fully dispersed, silica powder was added and stirring was continued for 15 minutes to obtain the plugging agent.

[0082] Example 8

[0083] A salt- and temperature-resistant hybrid hydrogel plugging agent comprises the following components by mass:

[0084] Acrylamide (AM) 2g, chain enhancer pregelatinized starch 2g, N-hydroxymethylacrylamide (NHMA) 2g, crosslinking agent N,N'-methylenebisacrylamide (MBA) 0.1g, nano-fumed silica 2.5g, sustained-release capsule initiation system 1.5g, formation water (mineralization 2.1×10⁻⁶) 5 92.5g (mg / L).

[0085] The preparation method of the sustained-release capsule initiation system is the same as in Example 1.

[0086] The preparation method of the above-mentioned plugging agent includes the following steps:

[0087] Chain enhancer pregelatinized starch, acrylamide (AM), N-hydroxymethylacrylamide (NHMA), crosslinking agent N,N'-methylenebisacrylamide (MBA), and sustained-release capsule initiation system were added sequentially to the formation water. After stirring until fully dispersed, nano-fumed silica was added, and stirring was continued for 15 minutes to obtain the plugging agent.

[0088] Example 9

[0089] A salt- and temperature-resistant hybrid hydrogel plugging agent, as described in Example 1, except that: in the preparation method of the sustained-release capsule initiation system, the amount of acrylic acid (AA) is 5g, the amount of hydrophobic monomer (octadecyl dimethyl allyl ammonium chloride) is 3g, and the amount of vinylpyrrolidone (NVP) is 10g.

[0090] Other steps, conditions, and raw material composition are the same as in Example 1.

[0091] The preparation method of the above-mentioned plugging agent is the same as that in Example 1.

[0092] Example 10

[0093] A salt- and temperature-resistant hybrid hydrogel plugging agent, as described in Example 1, except that in the preparation method of the sustained-release capsule initiation system, the amount of acrylic acid (AA) is 10g, the amount of hydrophobic monomer (octadecyl dimethyl allyl ammonium chloride) is 8g, and the amount of vinylpyrrolidone (NVP) is 15g.

[0094] Other steps, conditions, and raw material composition are the same as in Example 1.

[0095] The preparation method of the above-mentioned plugging agent is the same as that in Example 1.

[0096] Example 11

[0097] A salt- and temperature-resistant hybrid hydrogel plugging agent, as described in Example 1, except that the amount of tert-butyl hydroperoxide (TBHP) used in the preparation method of the sustained-release capsule initiation system is 17.5g.

[0098] Other steps, conditions, and raw material composition are the same as in Example 1.

[0099] The preparation method of the above-mentioned plugging agent is the same as that in Example 1.

[0100] Comparative Example 1

[0101] A plugging agent, as described in Example 1, except that the sustained-release capsule initiation system is replaced with 0.25 g tert-butyl hydroperoxide (TBHP); the other raw material composition is the same as in Example 1.

[0102] The preparation method of the above-mentioned plugging agent is the same as that described in Example 1, except that it is the same as above.

[0103] Comparative Example 2

[0104] A plugging agent, as described in Example 1, except that: no sustained-release capsule initiation system is added; the other raw material composition is the same as in Example 1.

[0105] The preparation method of the above-mentioned plugging agent is the same as that described in Example 1, except that it is the same as above.

[0106] Comparative Example 3

[0107] A plugging agent, as described in Example 1, except that no chain reinforcing agent is added; the other raw material composition is the same as in Example 1.

[0108] The preparation method of the above-mentioned plugging agent is the same as that described in Example 1, except that it is the same as above.

[0109] Comparative Example 4

[0110] A plugging agent, as described in Example 1, except that 2-acrylamido-2-methylpropanesulfonic acid (AMPS) is not added; the other raw materials are the same as in Example 1.

[0111] The preparation method of the above-mentioned plugging agent is the same as that described in Example 1, except that it is the same as above.

[0112] Comparative Example 5

[0113] A plugging agent, as described in Example 1, except that: no nano-fumed silica is added; the other raw material composition is the same as in Example 1.

[0114] The preparation method of the above-mentioned plugging agent is the same as that described in Example 1, except that it is the same as above.

[0115] Comparative Example 6

[0116] A plugging agent, as described in Example 1, except that the hydrophobic monomer (octadecyl dimethyl allyl ammonium chloride) and vinylpyrrolidone (NVP) are not added in the preparation method of the sustained-release capsule initiation system;

[0117] Other steps, conditions, and raw material composition are the same as in Example 1.

[0118] The preparation method of the above-mentioned plugging agent is the same as that in Example 1.

[0119] Experimental Example 1

[0120] Performance evaluation of water-blocking agents

[0121] The plugging agents obtained in the examples and comparative examples were subjected to performance tests. The gelation time test method was as follows: the time required for the system to transform from a flowable solution to a non-flowable gel under constant temperature of 140℃; specifically, the gelation determination point was observed when the Sydansk gel strength code F or higher (non-flowing when poured) was reached using the bottle test method. The Sydansk gel strength code method was used to evaluate the gelation strength. The Sydansk gel strength code is used to characterize gel flowability / deformability, with codes increasing progressively from A to I (or J): A is non-gelled; B is highly flowable gel; C is flowable gel; D is moderately flowable gel; E is almost non-flowable gel; F is highly deformable but non-flowable gel; G is moderately deformable but non-flowable gel; H is slightly deformable but non-flowable gel; I is rigid gel; J is a "ringing" rigid gel (resonant echo when tapped). The strength codes were evaluated after aging at 140℃ for 24 h. The elastic modulus was also tested after aging at 140℃ for 24 h. The elastic modulus was tested using a rheometer. The results are shown in Table 1.

[0122] Table 1 Elastic Modulus Test Table

[0123]

[0124] According to the experimental results in Table 1:

[0125] (1) Examples 1 to 8 of the present invention can all successfully gel at a high temperature of 140°C. By adjusting the amount of sustained-release capsule initiation system and other reactive monomers, the gelation time can be effectively controlled within the construction safety window of 4 to 6 hours. In contrast, Comparative Example 1 uses the method of directly adding initiator. The initiator decomposes rapidly at high temperature, causing the system to "burst polymerize" within 1 hour. The gelation time is out of control, and the resulting gel structure is uneven and has poor performance.

[0126] (2) This invention constructs a high-strength, high-elasticity gel network through the synergistic effect of acrylamide, chain reinforcing agent, multi-active-site reactive monomer, crosslinking agent N,N'-methylenebisacrylamide, and inorganic materials. The inorganic support material significantly improves the elastic modulus of the system. The gel strength code of Example 1 reaches H level (rigid gel), and the elastic modulus reaches 2180 Pa.

[0127] (3) Chain enhancers (modified starch) and multi-active-site reactive monomers are crucial for improving performance. This demonstrates their indispensability for forming a stable network structure. Comparative Example 2 failed to gel due to the lack of an initiation system, proving that the initiation step is a necessary condition for forming a gel network.

[0128] (4) The composition ratio of the sustained-release capsule initiation system has an important influence on its controlled-release performance. Example 7 used micron-sized silica powder, which significantly reduced its elastic modulus and strength. The micron-sized filler has poor compatibility with the polymer matrix and may become a stress concentration point. Examples 9 and 10 show that the amount of wall material monomer can be adjusted within a certain range to adjust the gelation time, while the amount of core material initiator should not be too much to avoid excessive polymerization leading to a predominance of short chains and affecting performance (Example 11). (5) Chain reinforcing agents, multi-active-site reactive monomers, and inorganic structural support materials each make indispensable contributions to the toughness, temperature resistance, salt resistance, and rigidity of the gel. Comparative Examples 3, 4, and 5 show that the absence of any component will lead to a significant decrease in the overall performance of the gel. (6) The sustained-release capsule initiation system must rely on hydrophobic associative polymer wall materials to achieve the sustained-release function. Comparative Example 6 lost the core advantage of controllable gelation time.

[0129] Experimental Example 2

[0130] The plugging performance was evaluated using a core displacement / fractured sandpipe simulation device. Several artificial sandstone cores (or natural cores) were selected, and the length L, diameter D, and initial permeability k0 were recorded. Formation water was injected at a constant rate at 140°C to obtain the baseline pressure difference ΔP0. Subsequently, the plugging agent working fluid prepared by the method of Example 1 of this invention was injected to a set PV number (PV is the pore volume, calculated based on the core pore volume), and allowed to age at 140°C for 24 hours until complete gelation. Then, formation water was used for reverse displacement, and the maximum pressure difference ΔP before breakthrough was recorded. max Reverse breakout of the pressure gradient according to ΔP max Calculate / L and perform at least 3 parallel tests and take the average value.

[0131] The sealing test results of the prepared hydrogel plugging agent are shown in the figure below. Figure 4 As shown, the reverse breakthrough pressure gradient reached 5.5 MPa / m, indicating that the plugging agent effectively blocked the pores, and the mechanical strength of the plugging agent met the requirements for sealing the fracture channels. In the plugging test, the pressure increased with the increase of the injected PV number, indicating that the plugging agent gradually accumulated and sealed in the pores until it reached its maximum plugging capacity.

[0132] Experimental Example 3

[0133] The mechanical properties of the samples prepared in Example 1 after curing in a 140℃ constant temperature oven for 4 hours were evaluated using a HY-0580 gel compressive strength testing machine. The fully gelled samples were cut and trimmed into uniform cylindrical specimens (approximately 25 mm in diameter and 45 mm in height), placed in the center of the testing machine's pressure plate, and subjected to an axial compressive load at a constant displacement rate of 10 mm / min. The stress-strain curves were recorded.

[0134] Test results are as follows Figure 5As shown, the peak compressive strength of this hydrogel is higher than 0.076 MPa, and its volume deformation capacity is greater than 70%, indicating that it has excellent rigidity and high elastic recovery characteristics. Its mechanical properties meet the stringent requirements of sealing materials for strength and deformation capacity under high temperature and high salt conditions.

[0135] Test Example 4

[0136] The density of the plugging agent working fluid prepared in Example 1 was determined using an ET-320M multi-functional densitometer from the Instrumentno brand. Its density at room temperature was 1.134 g / cm³. 3 .

[0137] Its rheological properties were determined using a HAAKE RS600 rheometer (coaxial cylindrical measuring system, DG41-Ti rotor) from Germany. Figure 6 Left image, within 10-1000 s -1 At the shear rate, the viscosity ranges from 100 to 800 mPa·s, exhibiting typical shear dilution behavior. Further temperature scanning tests were performed using a Viscotester iQ AIR Hack rheometer (CC25 DIN Ti rotor). Figure 6 As shown in the right figure, the working fluid viscosity remained between 40 and 800 mPa·s within the temperature range of 20-80℃, exhibiting good temperature stability and flow characteristics. These results indicate that the plugging agent working fluid of Example 1 has suitable density and excellent rheological properties, facilitating on-site mixing and safe pumping, and can meet the injection requirements under high-temperature and high-salinity reservoir conditions.

[0138] The salt-resistant, high-temperature-resistant, multi-stage, multi-layered hybrid hydrogel plugging agent provided by this invention, through its unique component design, especially benefiting from the sustained-release capsule initiation system and organic-inorganic hybrid structure, successfully solves the technical problems of uncontrolled gelation time, insufficient strength, and poor stability of traditional gels under high temperature and high salt conditions. It has excellent comprehensive performance and is suitable for plugging operations under harsh reservoir conditions.

[0139] While the present invention has been described with reference to specific embodiments, those skilled in the art will understand that various changes can be made without departing from the true spirit and scope of the invention. Furthermore, numerous modifications can be made to the subject, spirit, and scope of the invention to suit specific situations, materials, material compositions, and methods. All such modifications are included within the scope of the claims of the present invention.

Claims

1. A salt- and temperature-resistant hybrid hydrogel plugging agent, characterized in that, The composition includes the following components in parts by mass: Acrylamide 1.5-3 parts, chain reinforcer 1.5-2.5 parts, multi-active site reactive monomer 1.5-2.5 parts, crosslinking agent N,N'-methylenebisacrylamide 0.08-0.15 parts, inorganic structural support material 2-3 parts, slow-release initiation system 0.8-1.8 parts, formation water 90-95 parts; The chain enhancer is pregelatinized starch; the multi-active-site reactive monomer is selected from one or more combinations of 2-acrylamido-2-methylpropanesulfonic acid, N-hydroxymethylacrylamide, or N-hydroxymethylmethylacrylamide; the inorganic structural support material is a silicon-containing inorganic structural support material; the preparation method of the sustained-release initiation system includes the following steps: dissolving acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, vinylpyrrolidone (NVP), sodium formate, urea, and tert-butyl hydroperoxide (TBHP) in deionized water, adjusting the pH to 7.0, adding ammonium persulfate, reacting, shearing and pulverizing, drying, and sieving to obtain the sustained-release initiation system; the reaction temperature is 35-45℃, the reaction time is 4-6 hours, and the reaction is carried out under anaerobic protective gas protection and stirring conditions; the protective gas is nitrogen or argon; the formation water salinity is 0.5×10⁻⁶. 5 -2.5×10 5 mg / L.

2. The salt- and temperature-resistant hybrid hydrogel plugging agent according to claim 1, characterized in that, The inorganic structural support material is selected from one or more of nano-silica, silica sol, silica powder, or layered silicate minerals; the nano-silica is selected from one or two of precipitated silica or fumed silica.

3. The salt- and temperature-resistant hybrid hydrogel plugging agent according to claim 1, characterized in that, In the preparation method of the sustained-release initiation system, the mass ratio of acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, and vinylpyrrolidone (NVP) is 45:5-10:3-8:10-15; the mass ratio of acrylamide (AM), sodium formate, and urea is 45:1-5:1-5; and the mass ratio of acrylamide to deionized water is 45:150-250.

4. The salt- and temperature-resistant hybrid hydrogel plugging agent according to claim 3, characterized in that, The mass ratio of acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, and vinylpyrrolidone (NVP) is 45:8:5:12; the mass ratio of acrylamide (AM), sodium formate, and urea is 45:2:3; and the mass ratio of acrylamide to deionized water is 45:

200.

5. The salt- and temperature-resistant hybrid hydrogel plugging agent according to claim 1, characterized in that, In the preparation method of the sustained-release initiation system, the mass of ammonium persulfate is 0.5-1% of the total mass of acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, and vinylpyrrolidone (NVP).

6. The salt- and temperature-resistant hybrid hydrogel plugging agent according to claim 1, characterized in that, In the preparation method of the sustained-release initiation system, the mass of tert-butyl hydroperoxide (TBHP) is 20-25% of the total mass of acrylamide (AM), acrylic acid (AA), octadecyl dimethyl allyl ammonium chloride, and vinylpyrrolidone (NVP).

7. The salt- and temperature-resistant hybrid hydrogel plugging agent according to claim 1, characterized in that, The preparation method of the sustained-release initiation system includes one or more of the following conditions: i. Adjust the pH using a 5-15 wt% sodium hydroxide aqueous solution; ii. Sieve through a 100-mesh sieve.

8. The method for preparing the salt- and temperature-resistant hybrid hydrogel plugging agent according to any one of claims 1-7, characterized in that, Including the following steps: Chain enhancer, acrylamide (AM), multi-active-site reactive monomer, crosslinking agent N,N'-methylenebisacrylamide, and slow-release initiation system are added sequentially to the formation water, and the mixture is stirred continuously until it is fully mixed and dispersed. Then, inorganic structural support material is added and fully dispersed to obtain salt-resistant and temperature-resistant hybrid hydrogel plugging agent.

9. The application of the salt- and temperature-resistant hybrid hydrogel plugging agent as described in any one of claims 1-7 in reservoir water plugging.

Citation Information

Patent Citations

  • Controllable cross-linked gel plugging agent and preparation method thereof

    CN111117582A

  • Composition for preparing plugging agent, plugging agent as well as preparation method and application of plugging agent

    CN117624479A

  • Preparation method and application of microcapsule delayed initiation gel system

    CN118165181A